One-Local Retract and Common Fixed Point in Modular Metric Spaces - Afrah A. N. Abdou (Abstract and Applied Analysis)
The notion of a modular metric on an arbitrary set and the corresponding modular spaces, generalizing classical modulars over linear spaces like Orlicz spaces, were recently introduced. In this paper we introduced and study the concept of one-local retract in modular metric space. In particular, we investigate the existence of common fixed points of modular nonexpansive mappings defined on nonempty -closed -bounded subset of modular metric space.